Derek Parfit and yearning for personal identity (we do not exist, but really want to) - U. V. Dobronravova (Омский научный вестник: Серия "Общество. История. Современность")
The article critically represents Derek Parfit’s view on personal identity and its connection with our bodies. During the discussion with animalists who claim that persons are identical with bodies Parfit defends Lockean view and concludes that person isn’t identical with human being and easily can exist beyond it. Yet it seems obvious that person isn’t identical with body, such views lead to the controversial effects. For example, Parfit claims that abortion or euthanasia wouldn’t be a crime. This article discusses some of the most debatable basics of Parfit’s position and suggests at least three points worth of next thinking. At first, the author highlights that the so-called psychological criterion of personal identity is rather conventional. At second, the real experience of personal life doesn’t match with the famous Lockean definition, because we have no any continuity. At third, D. Parfit doesn’t explain what it means to be an animal (or human animal). If there is some biological «base» of a person (head, cerebrum, or part of a cerebrum), it still stays an animal. In the conclusion of the article the author suggests that we are not human beings, nor persons. But it doesn’t mean that we can’t become them